Notarist Affairs Reviewed By Law And Notary Department - Filianty; Habib Adjie (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
According to article 12 letter a of the Notary Law, notaries can be dishonorably dismissedbecause they have been declared bankrupt based on a court decision that has permanent legal force. This dishonorable dismissed is a treatment that is not in accordance with the concept of bankruptcy because the bankruptcy law itself regulates legal remedies to protect the interests of creditors as regulated in article 24 paragraph 1 of the Law on Bankruptcy. So there is a conflict between the two laws regarding the relevance of dismissal of a notary. This journal discusses whether the provisions in article 12 letter a of the Law of Notary do not conflict with Law on bankruptcy relating to the dismissal of a notary person who has been declared bankrupt by the Minister and. The purpose of this journal is to find out whether the provisions in article 12 letter a of the Law on Notary Position are not in conflict with Law on bankruptcy related to whether the notary can be dismissed from his position if he has been declared bankrupt by the court and the decision has permanent legal force. This journal uses the theory of legal certainty and theory of justice. This journal is a normative juridical study using a Legislative and Conceptual Approach. The result of the writing of this journal is that there is an inconsistency between the Law of Notary and Law ong Bankruptcy because the purpose and spirit of the law are different and dismissal of a notary from his position is irrelevant when viewed from the theory of justice and legal certainty..